Risk Factors of Acute Gastroenteritis and the Implementation of Community-Based Total Sanitation in Banyuwangi, Indonesia: A Cross-sectional Study - Al Karina, Citra; Juniastuti, Juniastuti; Utomo, Budi; Mertha Adnyana, I Made Dwi (Makara Journal of Health Research, 2025)
Background: In Banyuwangi Regency, Indonesia, diarrhea remains a major health problem, even though the community-based total sanitation (CBTS) program has been implemented for ten years. This household survey study aimed to identify the risk factors of acute gastroenteritis (AGE) and to evaluate the implementation of CBTS in Banyuwangi Regency. Methods: A cross-sectional study was conducted in Banyuwangi Regency. Characteristic data from patients with AGE were collected from the two primary healthcare working areas, followed by collecting data of their family members and CBTS in their houses. Data were obtained through interviews and direct observation. The CBTS evaluation results were analyzed descriptively, while risk factors were analyzed statistically using Chi-square and logistic regression tests. Results: Data were collected from 278 individuals across 96 families. Age and educational level were significantly associated with AGE. Individuals aged ≥19 years were less likely to have AGE (p < 0.001, OR = 0.385, 95% CI = 0.228-0.651). Most households had poor CBTS facilities of handwashing (76.0%), garbage (80.2%), and liquid waste disposal (88.5%). Conclusion: Age and education level were identified as individual risk factors for AGE. Most households had three poor facilities of CBTS. These findings might be considered in public health interventions to reduce AGE incidence in Banyuwangi Regency.